2020
DOI: 10.1155/2020/5647273
|View full text |Cite
|
Sign up to set email alerts
|

The Unusual Late-Onset Graves’ Disease following Hashimoto’s Related Hypothyroidism: A Case Report and Literature Review

Abstract: Background. The shift of Graves’ disease (GD) to Hashimoto’s disease- (HD-) related hypothyroidism is well established. However, the opposite is rare. This is likely to the loss of critical thyroid mass available for stimulation by thyroid hormone receptor stimulating antibody, making this shift unusual. Herein, we report a young lady with a late shift from HD into GD and present a scoping literature review. Case presentation. We report a twenty-five-year-old lady with a sixteen-year-history of Hashimoto’s-rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…On the contrary, Sukik et al 13 reported a very rare case of Hashimoto's thyroiditis shifting to Graves' disease after sixteen years from the initial diagnosis. Both Graves' disease and Hashimoto's thyroiditis share autoimmunity pathogenesis and the shift from one condition to another is possible 13 . However, the pathogenesis of Hashimoto's thyroiditis following Graves' disease has not been confirmed.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…On the contrary, Sukik et al 13 reported a very rare case of Hashimoto's thyroiditis shifting to Graves' disease after sixteen years from the initial diagnosis. Both Graves' disease and Hashimoto's thyroiditis share autoimmunity pathogenesis and the shift from one condition to another is possible 13 . However, the pathogenesis of Hashimoto's thyroiditis following Graves' disease has not been confirmed.…”
Section: Discussionmentioning
confidence: 98%
“…Hashimoto's thyroiditis manifested 7 to 25 years after the treatment of Graves' disease in three cases and after a few months in one patient. On the contrary, Sukik et al 13 reported a very rare case of Hashimoto's thyroiditis shifting to Graves' disease after sixteen years from the initial diagnosis. Both Graves' disease and Hashimoto's thyroiditis share autoimmunity pathogenesis and the shift from one condition to another is possible.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The diagnosis relies upon good history and physical exam followed by supportive antibody titers and radioiodine uptake scan. 39 Continuous evaluation of TSAb levels is recommended in HT, particularly in cases of TSAb-positive and those under replacement, since it may help predict conversion to GD. 40 Distinct immune paradigms, paucity of functioning tissue in long-standing HT, and infrequent conversion of blocking (TSBAb) to stimulating (TSAb) thyrotrophin receptor antibody (TRAb) may account for this.…”
Section: The Switch Between Gd and Htmentioning
confidence: 99%
“…5 In a large observational retrospective case series by Gonzalez-Aguilera et al in 2018, 1.2% of patients with hypothyroidism developed Graves' disease. 6 This conversion has been seen predominantly in middle-aged women. 7…”
Section: Questionmentioning
confidence: 99%